Problem Identification for Underwater Remotely Operated Vehicle (ROV): A Case Study - Abd Azis, Fadilah; Mohd Aras , Mohd Shahrieel; Ab Rashid, Mohd Zamzuri; Othman, Muhammad Nur; Abdullah, Shahrum Shah (2012)
This paper investigates and describes problem identification of Unmanned Underwater Remotely Operated Vehicle (ROV). The following is the problem identification that found after research done on several literature reviews and study cases. In this paper, the major problem statements will be discussed in details such as control system, underactuated condition, pose recovery or station keeping, coupling issues and communication technique. ROV is one of the Unmanned Underwater Vehicle (UUV) tethered with umbilical cable and remotely operated by a vehicle operator’s. Control system of ROV is a bit complex because of the unknown non-linear hydrodynamics effects, parameters uncertainties and the lack of a precise model of the ROV dynamics and parameters. Conventional controller cannot dynamically compensate for unmodeled vehicle hydrodynamic forces or unknown disturbances. Underactuated condition is defined as one having less control inputs than degree of freedom, so how the ROV want to maintain a certain point or depth following mission when one or more of thrusters malfunction also an issue to be highlighted. Pose recovery or station keeping will be one of the issues in ROV design. This station keeping approach is used to maintain a position in relation to another moving ROV as the ROV tries to remain stationary at the desired depth with present the environmental disturbances such as wind, waves, current and unexpected environmental disturbances. Coupling issue between the tether and cable with ROV body will be one problem in stabilizing the ROV itself as it double the vehicle load. . The underwater vehicle size, weight and operating depth, as well as the underwater vehicle motors, subsystems, and payload, all combine to determine the ROV’s cable design. In underwater, the inability of wireless communication system fails to work very well to transmit the video stream even in short distance is another issue to be covered. This statement proved by Underwater Technology Research Group student’s project. The experiment sets upthree types of sensor using wireless communication system for higher frequency such as video stream, data transfer and GPS.